Sensitive monitoring of the main metabolites of tri-(2-ethylhexyl) trimellitate (TOTM) in urine by coupling of on-line SPE, UHPLC and tandem mass spectrometry - Kuhlmann, Laura; Göen, Thomas; Eckert, Elisabeth (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2021)
Tri-(2-ethylhexyl) trimellitate (TOTM or TEHTM) is a substitute for the plasticizer di-(2-ethylhexyl) phthalate (DEHP). Here, a fast and sensitive UHPLC-MS/MS method is presented enabling the simultaneous quantification of the six main TOTM metabolites in urine. These include the primary metabolites 1-MEHTM and 2-MEHTM (1-/2-mono-(2-ethylhexyl) trimellitate) and two oxidized metabolites of each to ensure a precise determination and comparison of the regioselective pathways. The method is based on online enrichment of the analytes after enzymatic hydrolysis with subsequent UHPLC separation and tandem mass spectrometry using isotopically labeled internal standards. The method is distinguished by its high sensitivity with detection limits ranging from 0.01 to 0.04 µg/l and a proficient precision with relative standard deviations well below 10% for each analyte. The application of UHPLC-MS/MS analysis proved to significantly enhance the sensitivity of the method due to the efficient separation of the regioisomeric structures of the TOTM metabolites considered. Additionally, a proficient repeatability and recovery was achieved by the use of structurally identical isotopically labeled internal standard substances. The method was successfully applied to urine samples of infant patients indicating urinary levels of the TOTM metabolites examined in a very low concentration range.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Biomarker; Biomonitoring; Medical devices; Plasticizer; TEHTM; Urine